Branched-chain amino acids and L-alanine supplementation ameliorate calcium dyshomeostasis in sarcopenia: New insights for nutritional interventions - Conte, Elena; Mantuano, Paola; Boccanegra, Brigida; Imbrici, Paola; Dinoi, Giorgia; Lenti, Roberta; Cappellari, Ornella; Cappetta, Donato; De Angelis, Antonella; Berrino, Liberato; Gordish-Dressman, Heather; Bianchini, Gianluca; et al. (Frontiers in Pharmacology, 2024)
Introduction: During aging, sarcopenia and decline in physiological processes lead to partial loss of muscle strength, atrophy, and increased fatigability. Muscle changes may be related to a reduced intake of essential amino acids playing a role in proteostasis. We have recently shown that branched-chain amino acid (BCAA) supplements improve atrophy and weakness in models of muscle disuse and aging. Considering the key roles that the alteration of Ca2+-related homeostasis and store-operated calcium entry (SOCE) play in several muscle dysfunctions, this study has been aimed at gaining insight into the potential ability of BCAA-based dietary formulations in aged mice on various players of Ca2+ dyshomeostasis. Methods: Seventeen-month-old male C57BL/6J mice received a 12-week supplementation with BCAAs alone or boosted with two equivalents of L-alanine (2-Ala) or with dipeptide L-alanyl-L-alanine (Di-Ala) in drinking water. Outcomes were evaluated on ex vivo skeletal muscles indices vs. adult 3-month-old male C57BL/6J mice. Results: Ca2+ imaging confirmed a decrease in SOCE and an increase of resting Ca2+ concentration in aged vs. adult mice without alteration in the canonical components of SOCE. Aged muscles vs. adult muscles were characterized by a decrease in the expression of ryanodine receptor 1 (RyR1), the Sarco-Endoplasmic Reticulum Calcium ATPase (SERCA) pump, and sarcalumenin together with an alteration of the expression of mitsugumin 29 and mitsugumin 53, two recently recognized players in the SOCE mechanism. BCAAs, particularly the formulation BCAAs+2-Ala, were able to ameliorate all these alterations. Discussion: These results provide evidence that Ca2+ homeostasis dysfunction plays a role in the functional deficit observed in aged muscle and supports the interest of dietary BCAA supplementation in counteracting sarcopenia-related SOCE dysregulation.